2011
DOI: 10.1029/2010jb007963
|View full text |Cite
|
Sign up to set email alerts
|

A large intraplate earthquake triggered by latent magmatism

Abstract: A magnitude (Mj) 7.3 intraplate earthquake occurred in the western Tottori area, southwest Japan, on 6 October 2000, where there was no apparent prefaulting subsurface indication of the source fault of the 2000 earthquake. Magnetotelluric soundings were taken in and around where the aftershocks occurred in order to image three‐dimensional electrical resistivity structure at depths of up to 40 km, which could indicate an anomalously conductive body in the middle crust to the upper mantle on the southwestern sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Beneath the active volcanoes along the volcanic front and back-arc areas in Kyushu, prominent low-velocity (low-V) zones are clearly visible in the crust and upper-mantle wedge above the subducting Philippine Sea slab, which reflect the source zones of arc and back-arc magmatism caused by the slab dehydration and corner flow (convection) in the mantle wedge Stern, 2002;Cagnioncle et al, 2007;Zhao et al, 2000Zhao et al, , 2011. Low-V zones are also visible in the crust and uppermost mantle above the slab under the fore-arc region of Kyushu, which reflect the slab dehydration and fore-arc mantle serpentinization because of the young and warm Philippine Sea slab Hyndman and Peacock, 2003;van Keken, 2003;Xia et al, 2008a;Hilairet and Reynard, 2009). The Sakura-Jima volcano is located at the southern edge of the present study area, and so the Philippine Sea slab and the structure of the crust and upper mantle are not imaged as well as those under the other active volcanoes in Kyushu.…”
Section: Analysis and Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Beneath the active volcanoes along the volcanic front and back-arc areas in Kyushu, prominent low-velocity (low-V) zones are clearly visible in the crust and upper-mantle wedge above the subducting Philippine Sea slab, which reflect the source zones of arc and back-arc magmatism caused by the slab dehydration and corner flow (convection) in the mantle wedge Stern, 2002;Cagnioncle et al, 2007;Zhao et al, 2000Zhao et al, , 2011. Low-V zones are also visible in the crust and uppermost mantle above the slab under the fore-arc region of Kyushu, which reflect the slab dehydration and fore-arc mantle serpentinization because of the young and warm Philippine Sea slab Hyndman and Peacock, 2003;van Keken, 2003;Xia et al, 2008a;Hilairet and Reynard, 2009). The Sakura-Jima volcano is located at the southern edge of the present study area, and so the Philippine Sea slab and the structure of the crust and upper mantle are not imaged as well as those under the other active volcanoes in Kyushu.…”
Section: Analysis and Resultsmentioning
confidence: 98%
“…LF events occurred both before and after the 2000 Tottori earthquake in the focal area (Ohmi and Obara, 2002). It was suggested that the generation of the 2000 western Tottori earthquake was affected by the hot magma under the Daisen volcano and fluids from dehydration of the subducting Philippine Sea slab Sun et al, 2008;Gupta et al, 2009;Umeda et al, 2011). These pieces of evidence indicate that the Daisen volcano is still active and there exists magmatic activity beneath it.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Previously published helium isotope data used in this study are from Craig et al [1978], Doğan et al [2006], Kita et al [1993], Kusakabe et al [2003], Marty et al [1989], Matsumoto et al [2003], Morikawa et al [2005], Murakami [2010], Nagao [2004], Nagao et al [1981], New Energy and Industrial Technology Development Organization [1988, 1990], Notsu et al [2001], Ohno et al [2011], Ohwada et al [2007], Okada et al [1994], Ono et al [1993], Sakamoto et al [1992], Sakata et al [1987], Sano and Wakita [1985], Sano and Marty [1995], Sano et al [1982, 1984, 1986, 1998a, 1998b, 2006, 2009], Sato et al [2002], Sturchio et al [1996], Takahata et al [2003], Umeda and Ninomiya [2009], Umeda et al [2006a, 2006b, 2007a, 2007b, 2009a, 2009b, 2011a, 2011b, 2012], Wakita et al [1987], and K. Asamori et al (unpublished data, 2012). The majority of samples measured in the previous studies were collected from wells and bubbling natural springs, the remainder are from volcanic gases.…”
Section: Discussionmentioning
confidence: 99%
“…The large, low seismic velocity zone in the upper mantle is ascribed to the combined effects of chemical composition, thermal anomaly and fluid contents, indicating an upwelling asthenosphere acting as a primary source of magmas in southwest Japan [ Nakajima and Hasegawa , 2007b]. Recently, 3‐D magnetotelluric soundings imaged an anomalously large conductive body extending from the middle crust into the upper mantle to the west of Tottori City, indicating latent magmatism in the present‐day subduction system [ Umeda et al , 2011b]. Therefore, the anomalously high 3 He/ 4 He ratios observed in the northern Chugoku region could originate from the upward migration of magma and/or mantle‐derived fluids due to an upwelling asthenosphere (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation